FREQUENCY OF Î²-THALASSEMIA TRAIT IN FAMILIES OF THALASSEMIA MAJOR PATIENTS, LAHORE - Majeed, Tazeen; Akhter, Mohammed Adil; Nayyar, Ujala; Riaz, Muhammad Safwan; Mannan, Jovaria (Journal of Ayub Medical College Abbottabad, 2013)
Background: Thalassemia major is one of the most common genetic disorders in Pakistan and over five thousand new patients are added in the pool annually. This familial disease has both medical and social implications, and therefore there is a need to assess the magnitude of Î²-Thalassemia trait amongst family members of Thalassemia major patients. Methods: This cross-sectional descriptive study enrolled 674 blood samples from first degree relatives of registered patients of Thalassemia major at Sir Ganga Ram Hospital, Lahore. Peripheral blood smears were studied for abnormal morphology findings of microcytosis, hypochromia, poikilocytosis (tear drops, target cells) and Erythrocyte indices (haemoglobin, RBCs, mean corpuscular haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin concentration) and Hb electrophoretic (HbA, HbA2, & HbF). Results: Hb electrophoresis showed 61% of the study subjects had haemoglobinopathies. Frequency of Î²-Thalassemia trait was highest followed by Î²-Thalassemia major, HbE trait, HbD Punjab and Hb intermedia. Conclusion: Findings strongly suggest screening for Î²-Thalassemia trait in families of Thalassemia major patients. Keywords: Thalassemia Trait, Hb electrophoresis, Haemoglobinopathies